Phylogenetic characterization of β-tubulins and development of pyrosequencing assays for benzimidazole resistance in cattle nematodes. - Janina Demeler (Public Library of Science (PLoS), 2013)
Control of helminth infections is a major task in livestock production to prevent health constraints and economic losses. However, resistance to established anthelmintic substances already impedes effective anthelmintic treatment in many regions worldwide. Thus, there is an obvious need for sensitive and reliable methods to assess the resistance status of at least the most important nematode populations. Several single nucleotide polymorphisms (SNPs) in the β-tubulin isotype 1 gene of various nematodes correlate with resistance to benzimidazoles (BZ), a major anthelmintic class. Here we describe the full-length β-tubulin isotype 1 and 2 and α-tubulin coding sequences of the cattle nematode Ostertagia ostertagi. Additionally, the Cooperia oncophora α-tubulin coding sequence was identified. Phylogenetic maximum-likelihood analysis revealed that both isotype 1 and 2 are orthologs to the Caenorhabditis elegans ben-1 gene which is also associated with BZ resistance upon mutation. In contrast, a Trichuris trichiura cDNA, postulated to be β-tubulin isotype 1 involved in BZ resistance in this human parasite, turned out to be closely related to C. elegans β-tubulins tbb-4 and mec-7 and would therefore represent the first non-ben-1-like β-tubulin to be under selection through treatment with BZs. A pyrosequencing assay was established to detect BZ resistance associated SNPs in β-tubulin isotype 1 codons 167, 198 and 200 of C. oncophora and O. ostertagi. PCR-fragments representing either of the two alleles were combined in defined ratios to evaluate the pyrosequencing assay. The correlation between the given and the measured allele frequencies of the respective SNPs was very high. Subsequently laboratory isolates and field populations with known resistance status were analyzed. With the exception of codon 167 in Cooperia, increases of resistance associated alleles were detected for all codons in at least one of the phenotypically resistant population. Pyrosequencing provides a fast, inexpensive and sensitive alternative to conventional resistance detection methods.